Artificial reef design affects benthic secondary productivity and provision of functional habitat. Issue 4 (8th February 2020) - Rouse, Sally; Porter, Joanne S.; Wilding, Thomas A.
Abstract: Novel hard substratum, introduced through offshore developments, can provide habitat for marine species and thereby function as an artificial reef. To predict the ecological consequences of deploying offshore infrastructure, and sustainably manage the installation of new structures, interactions between artificial reefs and marine ecosystem functions and services must be understood. This requires quantitative data on the relationships between secondary productivity and artificial reef design, across all trophic levels. Benthic secondary productivity is, however, one of the least studied processes on artificial reefs. In this study, we show that productivity rates of a common suspension feeder, Flustra foliacea (Linnaeus 1758), were 2.4 times higher on artificial reefs constructed from "complex" blocks than on reefs constructed from "simple" blocks, which had a smaller surface area. Productivity rates were highest on external areas of reefs. Productivity rates decreased by 1.56%, per cm distance into the reef on complex reefs and 2.93% per cm into the reef on simple block reefs. The differences in productivity rates between reefs constructed from simple and complex blocks are assumed to reflect different current regimes and food supply between the external and internal reef areas, according to reef type. Synthesis and applications. Our results show that artificial reef design can affect secondary productivity at low trophic levels. We demonstrate that the incorporation of voids into reef blocks can lead to a greater proportion of the structure serving as functional habitat for benthic species. By including such modifications into the design of artificial reefs, it may be possible to increase the overall productivity capacity of artificial structures. Abstract : Artificial reef design can affect secondary productivity of organism low trophic levels. We demonstrate that the incorporation of voids into reef blocks can lead to a greater proportion of the structure serving as functional habitat for benthic species, and a higher overall productive output for the reef.